METHODS OF TEACHING PRIMARY CLASS STUDENTS TO SYSTEMATIC COMPOSITION OF INFORMATION - Begaliyeva Maftuna Faxridinovna (PEDAGOGS, 2025)
Annotation: The article highlights the issues that should be implemented in the education and formation of respect for our national values, which we should pay attention to in order to enlighten the culture of information and knowledge acquisition of primary school students, the purposeful use of hyper-environment technologies that are developing globally today.